COVID-19 Vaccinations, Infections, and Outcomes Among 784 People Living with HIV - Keren Mahlab-Guri; Irina Komarova; Laliv Kadar; Shay Nemet; Ramon Cohen; Sara Radian-Sade; Achiel Tova; Alex Guri; Shira Rosenberg-Bezalel; Daniel Elbirt (Viruses)
Introduction: Variants of COVID-19 are responsible for 700 million infections and 7 million deaths worldwide. Vaccinations have high efficiency in preventing infection and secondary benefits of reducing COVID-19 hospital admissions, attenuating disease severity and duration of illness. Conflicting reports were published regarding COVID-19 among PLWH. Objective: The aim of this study was to evaluate COVID-19 morbidity, hospitalization, and the magnitude of immunological response to sequential BNT 162b2 mRNA vaccines in PLWH regarding demographic and clinical factors. Results: Our retrospective study included 784 PLWH who had at least one anti- SARS-CoV-2 antibody test between March 2021 and October 2021. Half of our patients (392) had CD4 cell counts above 500 cells/µL, 40.2% (315) had 200 < CD4 < 500 cells/µL and only 9.8% (77) had CD4 < 200 cells/µL at their last laboratory workup. The mean age was 50.2 ± 12.2 years. About 90% of our patients were given at least two doses of the BNT 162b2 Pfizer vaccines; about 60% received three doses of the vaccine. About a quarter of our patients (27.6%) had COVID-19 infection. Only six patients required hospital admission. All six patients recovered from COVID-19 infection. Titers of COVID-19 antibodies were lower for patients with CD4 cell counts of less than 200 cells/µL in the first, second, and third serological tests with statistical significance. In a multinomial logistic regression, the influence of other factors such as age, sex, and previous COVID-19 infection on first COVID-19 antibody titers was not significant. Conclusions: PLWH are responsive to COVID-19 vaccines. As was expected, patients with higher CD4 cell counts had higher titers of COVID-19 antibodies and lower hospitalization rate. Age, sex, and previous COVID-19 infection did not significantly affect antibody titers according to our study. Larger prospective studies with control groups are needed to further characterize immunologic response to COVID-19 vaccination among PLWH.